The Effect of Elderly Fitness Exercises on Sleep Quality in Perimenopausal Women in the Working Area of Bintang Ninggi 1 Health Center - Risnawati Br. Surbakti; Reny Retnaningsih (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Sleep disturbances are one of the most common complaints experienced by perimenopausal women due to hormonal changes, decreased melatonin production, and increased sympathetic nervous system activity. The impact of sleep disturbances during this phase not only affects physical and psychological function, but also quality of life and daily productivity. Non-pharmacological interventions such as Senam Bugar Lansia (Elderly Fitness Exercise) are considered potential in improving sleep quality through stimulation of the parasympathetic nervous system, increased endorphins, and regulation of circadian rhythms. This study aims to analyze the effect of Senam Bugar Lansia on sleep quality in perimenopausal women in the Bintang Ninggi 1 Community Health Center (Pustu Bintang Ninggi 1) Work Area. The study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 respondents selected using a total sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. The results showed a decrease in PSQI scores from 11.4 to 6.2 after the intervention, and statistical tests showed a significant difference (p < 0.001). These findings indicate that Senam Bugar Lansia (Elderly Fitness Exercise) is effective in improving sleep quality in perimenopausal women. Senam Bugar Lansia can be recommended as a routine, community-based intervention to improve sleep quality and well-being in perimenopausal women.